Sistem Informasi Pendaftaran Peserta Didik Baru Berbasis Web Pada SMP Negeri 2 Wanukaka - Matius Laiya Motu; Elfira Umar; Agustina Purnami Setiawi (Journal Of Informatics And Busisnes, 2024)
SMP Negeri 2 Wanukaka is one of the educational institutions in West Sumba Regency. The purpose of designing and implementing this web-based new student registration information system is due to the lack of information to prospective new students regarding information on the new student registration process such as registration flow, information on registration fees and so on. So by designing this information system prospective new students can access new student registration information online so that prospective new students do not have to go to school to get registration information. In designing this web-based new student registration information system using the PHP and MySQL programming languages as database servers which have been summarized in one XAMMP application, the system design uses the waterfall method which consists of analysis, system design, coding and testing. The aim of creating this system is to support the service process so that it can improve the quality of service in conveying information to the public and assist the school in processing data on prospective new students well. After implementing the system and user testing which was carried out using the interview method at the school, the results were obtained that the existence of this web-based new student registration information system can help prospective new students to receive and access online registration information, including information on registration requirements. , test schedule, registration fees, graduation announcements, as well as a test card feature that can be printed directly by prospective new students which will later be used as a requirement for taking the selection exam. It can also help the school in preparing new student reports online, so that the information provided is distributed more effectively and efficiently, and the processing of new student admissions data can be done more effectively.